2013
DOI: 10.1016/j.anorl.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

First bite syndrome

Abstract: Based on a review of the indexed medical literature (PubMed database), the authors describe the clinical features leading to the diagnosis of first bite syndrome, the pathophysiology of this syndrome and analyse the various treatment options available to otorhinolaryngologists to manage this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 19 publications
3
73
0
1
Order By: Relevance
“…Mastication will induce the release of parasympathetic neurotransmitters resulting in a supramaximal response to the myoepithelial cells. It is speculated that this supramaximal response, or contractile response, is what is responsible for the intense head and neck pain and/or cramps experienced by patients with FBS 4. This theory is consistent with findings by Chiu et al 2 and Kawashima et al ,11 as both found evidence to suggest that loss of sympathetic innervation to the parotid gland from the superior cervical ganglion (SCG) is a likely aetiological factor in FBS.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Mastication will induce the release of parasympathetic neurotransmitters resulting in a supramaximal response to the myoepithelial cells. It is speculated that this supramaximal response, or contractile response, is what is responsible for the intense head and neck pain and/or cramps experienced by patients with FBS 4. This theory is consistent with findings by Chiu et al 2 and Kawashima et al ,11 as both found evidence to suggest that loss of sympathetic innervation to the parotid gland from the superior cervical ganglion (SCG) is a likely aetiological factor in FBS.…”
Section: Discussionsupporting
confidence: 77%
“…The main class being postoperative syndromes, as more than 95% of published cases of FBS correspond to complications following surgeries,4 particularly parapharyngeal space dissections, resection of the deep lobe of the parotid gland and sacrifice of the sympathetic chain 9. In fact, Linkov et al 9 reported a 9.6% (n=45) cumulative incidence in 499 patients who had undergone such procedures, and found deep lobe parotidectomy to be the most common cause of FBS in this cohort.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Conversely, one patient treated with acupuncture seemed to receive no benefits from it. Intraparotid botulinum toxin injection appears to be the most effective first-line treatment option at the present time, although the injection protocol and its long-term efficacy have not yet been clearly defined, as it also merges from a recently published review of the indexed medical literature by Laccourreye et al [15] In the absence of randomized controlled trials or well established treatment strategies, we proposed to our patients an alternative treatment protocol that had already been successful in our ENT Department for patients with SS. We described the first two cases handled with acupuncture for FBS occurring after upper cervical surgery: a woman with pleomorphic adenoma of the deep lobe of the parotid gland and a man affected by cervical sympathetic chain neurinoma.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al tratamiento, hay que tener en cuenta que en muchos casos los pacientes presentan mejoría espontánea, por lo que un tratamiento agresivo puede ser innecesario [2][3][4] . En nuestra opinión, el empleo de la toxina botulínica es de primera elección ante un paciente con SPM.…”
Section: Figura 2 -A) Corte Axial En Secuencia T1 Con Gadolinio B) Cunclassified